MODERN CONCEPTS ON THE STRUCTURE OF LYMPH NODES (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The article presents an overview of the latest data on the structural and functional features of the lymph nodes - peripheral organs of the immune system involved in the body's immune response. The morphological and functional features of the zonal structure, features of intercellular relationships are described.